Dexmedetomidine alleviates intestinal ischemia/reperfusion injury by modulating intestinal neuron autophagy and mitochondrial homeostasis via Nupr1 regulation - Qiong Wu; Qiuhong Chen; Sisi Liang; Jinping Nie; Yingjie Wang; Chenlu Fan; Zhen Liu; Xuekang Zhang (BMC, 2024)
Abstract Intestinal ischemia/reperfusion injury (I/R) is a common yet challenging-to-treat condition, presenting a significant clinical challenge. This study aims to investigate the protective mechanisms of Dexmedetomidine (Dex) against I/R injury, with a particular focus on its role in regulating autophagy activity in intestinal neurons and maintaining mitochondrial homeostasis. Experimental findings demonstrate that Dex can mitigate intestinal damage induced by I/R through the modulation of autophagy activity and mitochondrial function in intestinal neurons by suppressing the expression of Nupr1. This discovery sheds light on a new molecular mechanism underlying the potential efficacy of Dex in treating intestinal I/R injury, offering valuable insights for clinical therapy.